PTEN augments SPARC suppression of proliferation and inhibits SPARC-induced migration by suppressing SHC-RAF-ERK and AKT signaling - Thomas, Stacey L. (Oxford University Press, 2010)
SPARC (secreted protein acidic and rich in cysteine) is expressed in all grades of astrocytoma, including glioblastoma (GBM). SPARC suppresses glioma growth but promotes migration and invasion by mediating integrin and growth factor receptor-regulated kinases and their downstream effectors. PTEN (phosphatase and tensin homolog deleted on chromosome 10), which is commonly lost in primary GBMs, negatively regulates proliferation and migration by inhibiting some of the same SPARC-mediated signaling pathways. This study determined whether PTEN reconstitution in PTEN-mutant, SPARC-expressing U87MG cells could further suppress proliferation and tumor growth but inhibit migration and invasion in SPARC-expressing cells in vitro and in vivo, and thereby prolong survival in animals with xenograft tumors. In vitro, PTEN reduced proliferation and migration in both SPARC-expressing and control cells, with a greater suppression in SPARC-expressing cells. PTEN reconstitution suppressed AKT activation in SPARC-expressing and control cells but suppressed the SHC-RAF-ERK signaling pathway only in SPARC-expressing cells. Importantly, coexpression of SPARC and PTEN resulted in the smallest, least proliferative tumors with reduced invasive capacity and longer animal survival. Furthermore, direct inhibition of the AKT and SHC-RAF-ERK signaling pathways suppressed the proliferation and migration of SPARC-expressing cells in vitro. These findings demonstrate that PTEN reconstitution or inhibition of signaling pathways that are activated by the loss of PTEN provide potential therapeutic strategies to inhibit SPARC-induced invasion while enhancing the negative effect of SPARC on tumor growth.